A comparative analysis of bacterial community characterization and host–bacteria interactions between bi-macroalgal blooms caused by Ulva prolifera and Sargassum horneri - Zang, Yu; Liu, Xiaoxue; Xue, Song; Yin, Lei; Fan, Shiliang; Miao, Xiaoxiang; Fu, Mingzhu; Xiao, Jie; Wang, Zongling (Frontiers in Microbiology, 2025)
Macroalgal blooms have increasingly occurred in coastal regions worldwide. Since 2017, simultaneous green tides (Ulva prolifera) and golden tides (Sargassum horneri) have recurred annually in the Yellow Sea, forming a unique large-scale bi-macroalgal bloom. Interactions between macroalgae and their associated bacterial communities are recognized as key ecological drivers of algal bloom dynamics. In this study, the differences in phycosphere-associated bacterial communities and algae-derived metabolites between U. prolifera and S. horneri were explored using the 16S rRNA amplicon combined with broad-spectrum metabolomics. The results reveal that the diversity of phycospheric and epiphytic bacterial communities of S. horneri is significantly higher than that of U. prolifera. We observed distinct phycosphere bacterial recruitment between the two macroalgal species. Verrucomicrobiae were the stable core microbiota in the U. prolifera phycosphere, whereas Gammaproteobacteria and Bacteroidia represented the core members in that of S. horneri. Community assembly analyses indicate that deterministic processes predominantly shape the epiphytic bacterial communities, suggesting strong host selection effects. Metabolomic profiling further revealed that the metabolites secreted by U. prolifera, such as phenolic acids and organic acids, promote the proliferation and colonization of Verrucomicrobiae Rubritalea, which may enhance the stress tolerance of the host. In contrast, the amino acids, nucleotides, lipids, and their derivatives are key metabolites that promote the colonization of Gammaproteobacteria Vibrio and Marinomonas on the S. horneri surface, which may inhibit host growth through the production of algicidal substances. Together, these results suggest that U. prolifera and S. horneri can secrete different metabolites that recruit epiphytic microbial communities and influence macroalgae–bacteria interactions. These findings provide insights into the ecological mechanisms underlying host–bacteria interactions and their roles in the formation and persistence of macroalgal blooms.